Crafting The Msmes’ Performance Into Financial Literacy, Financial Inclusion, and Fintech In Emerging Countries - Nu Graha, Andi; Asna, Asna; Anjar Puspitosari Suharso, Arien (International Journal of Science, Technology & Management, 2023)
The informal sector in Indonesia in terms of Micro, Small and Medium Enterprises (MSMEs) plays an important role in economic development from macro and micro aspects. The majority of SME owners are aware of the value of a number of strategies for conducting business more effectively. Some of the primary strategies for maintaining MSMEs performance include financial inclusion, financial literacy, and fintech. The objectives aimed at by this investigation were: to study the impact of financial inclusion and financial literacy on SME performances, to observe the influence of mediation effect fintech on financial inclusion and MSME performance, and to examine how the fintech supports financial literacy and SME performance. A well-structured questionnaire using a quantitative research approach was utilized to gather data from 320 owners among Indonesia MSMEs. The finding research revealed that fintech contributed positively and significantly mediates the relationship between financial inclusion, financial literacy, and MSMEs performance. The research's findings aim to shed light on how to develop and promote fintech through providing services that are fair and transparent.